Khānvādah va masāʻil-i hamsarān-i javān : mamūʻah-i baḥ̲sʻhā-yi rādiyūʻī nīmah-i avval-i sāl-i 1362 - Qāʼimī, ʻAlī (Intishārāt-i Amīrī, 1985)
On family life in post-revolution Iran, especially problems related to young spouses; collected speeches broadcast over Iranian radio in 1983.